2013
DOI: 10.1371/journal.pone.0073816
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sensing Receptor Expression in Ovine Amniotic Fluid Mesenchymal Stem Cells and the Potential Role of R-568 during Osteogenic Differentiation

Abstract: Amniotic fluid-derived stem (AFS) cells have been identified as a promising source for cell therapy applications in bone traumatic and degenerative damage. Calcium Sensing Receptor (CaSR), a G protein-coupled receptor able to bind calcium ions, plays a physiological role in regulating bone metabolism. It is expressed in different kinds of cells, as well as in some stem cells. The bone CaSR could potentially be targeted by allosteric modulators, in particular by agonists such as calcimimetic R-568, which may po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
2
12
1
Order By: Relevance
“…However, we suspect that the calcium sensing receptor (CaSR) may play a role in inhibiting chondrogenesis in response to increased extracellular calcium, as it has been shown to be expressed and functionally active in osteoblast-like cell lines 40 and several types of stem cells, including human and ovine amniotic fluid stem cells, 41 equine umbilical cord matrix, 42 and bone marrow mesenchymal stem cells (MSCs). 43 More recently, the calcium-sensing receptor was reported to play a potential role in the osteogenic differentiation of human amniotic fluid MSCs.…”
Section: Camentioning
confidence: 99%
“…However, we suspect that the calcium sensing receptor (CaSR) may play a role in inhibiting chondrogenesis in response to increased extracellular calcium, as it has been shown to be expressed and functionally active in osteoblast-like cell lines 40 and several types of stem cells, including human and ovine amniotic fluid stem cells, 41 equine umbilical cord matrix, 42 and bone marrow mesenchymal stem cells (MSCs). 43 More recently, the calcium-sensing receptor was reported to play a potential role in the osteogenic differentiation of human amniotic fluid MSCs.…”
Section: Camentioning
confidence: 99%
“…Wnt signaling is also involved in AFMSC commitment toward osteogenesis [13] . Recently, we identified for the first time, the presence of Calcium Sensing Receptor (CaSR) in ovine and human AFMSCs [44,68] . CaSR, originally cloned from parathyroid glands, acts by controlling the secretion of parathyroid hormone in response to changes in extracellular calcium levels [75] .…”
Section: In Vitro Osteogenic Differentiationmentioning
confidence: 99%
“…We have analyzed the fresh supernatant of MSC cultures, containing EVs displaying the phenotype of their parental cells. In order to identify the best marker to study MSC-derived EVs, we tested different MSC specific antibodies, as listed in Table S1 and we confirmed that, given that CD90 represents a well-recognized pan-MSC- marker, it is also well expressed on MSC-derived EVs [ 42 , 51 , 53 ]. Therefore, for each sample, 100 μL of MSC supernatant were stained using 3 μL (0.006 μg/μL) of an anti-human CD90 conjugated to R-phycoerythrin (PE) (BD Biosciences, San Jose, CA, USA; Clone 5E10, Cat.…”
Section: Methodsmentioning
confidence: 98%